Programmed Cell Death Ligand 1 Expression in Resected Lung Adenocarcinomas: Association with Immune Microenvironment. Issue 11 (November 2016) - Huynh, Tiffany G.; Morales‐Oyarvide, Vicente; Campo, Meghan J.; Gainor, Justin F.; Bozkurtlar, Emine; Uruga, Hironori; Zhao, Ling; Gomez‐Caraballo, Maria; Hata, Aaron N.; Mark, Eugene J.; Lanuti, Michael; Engelman, Jeffrey A.; et al.
ABSTRACT : Introduction : Programmed cell death ligand 1 (PD‐L1) expression on tumor cells can be upregulated via activation of CD8 + cytotoxic T lymphocytes (CTLs) or the T helper cell (Th1) pathway, counterbalancing the CTL/Th1 microenvironment. However, PD‐L1 expression in association with subtypes of tumor‐associated lymphocytes and molecular alterations has not been well characterized in lung adenocarcinomas. Methods : PD‐L1 expression was evaluated in 261 resected lung adenocarcinomas using tissue microarrays and various scoring systems, and was correlated with clinicopathologic/molecular features, including the extent/subtype of tumor‐associated lymphocytes (i.e., CD8, T‐bet [Th1 transcription factor], and GATA3 [Th2 transcription factor]), and patient outcomes. Results : PD‐L1 expression was present in 129 (49%), 95 (36.5%), and 62 (24%) cases using cutoffs of ≥1%, ≥5%, and ≥50%, respectively, 98 (38%) by H score and 72 (28%) by immune score. PD‐L1 expression was associated with abundant CD8 + and/or T‐bet + tumor‐infiltrating lymphocytes and EGFR wild‐type, significant smoking history, and aggressive pathologic features. In addition, concurrent PD‐L1 expression and abundant CD8 + tumor‐associated lymphocytes were seen in 25% of KRAS mutants or cases with no alterations by clinical molecular testing as opposed to only 7.4% of EGFR mutants. PD‐L1 expression was significantly associated with decreased progression‐free and overall survival rates by univariate analysis, but not by multivariate analysis. Conclusion : PD‐L1 expression in resected lung adenocarcinomas is frequently observed in the presence of CTL/Th1 microenvironment, in particular in those with KRAS mutations or no common molecular alterations, suggesting that blockade of the PD‐1/PD‐L1 axis may be a promising treatment strategy to reinstitute active immune response for at least a subset of such patient populations.